The Paradox of Elite Law Schools in India—A comparison with Canadian Legal Education - Dasgupta, Upasana (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2019)
Legal education, like law, should always be overhauled and refitted to changes in society. What is sought is a model of legal education that best meets the needs of the society, by law students and law professionals alike. In 1987, a new model of law school was established in Bengaluru, India—the National Law School of India University (NLSIU)—drawing largely upon components of the Socratic method and the case-study method that had already been implemented, tried and tested in North America. This paper is a comparison of legal education in North America, particularly in Canada, and in the National Law Universities (NLUs) in India, based on the model of NLSIU. The comparison identifies similarities and dissimilarities between legal education of two countries, India and Canada, one developed and one developing, both of which imbibed the Harvard case method at some point in time. The object of the study is to point out the paradoxes existing in legal education in general and the NLU system in India and is a preliminary study of whether Canadian law schools and NLU systems can learn lessons from each other.At one time—when law-school education was characterized by disinterested practitioners and academicians lecturing a passive group of students and evaluating them through closed-book examinations, where students needed to spend time memorizing the law instead of analyzing it—NLUs were a welcome experiment. They changed the face of legal education by encouraging discussion in class; incorporating an interdisciplinary approach, introducing research projects, compulsory internships and introducing many other innovations. With time, these innovations proved to be less effective and perhaps the time is ripe for change in legal education in India, as in the words of Roscoe Pound, “[w]e must seek principles of change no less than principles of stability.”